Abordagem temática: um olhar para a apreensão de temas - Klein, Sabrina Gabriela (2021)
The present investigation aims to answer the research problem: What are the contributions and limits of the Thematic Approach, in the area of natural sciences, for the apprehension of themes? In this sense, the general objective is to analyze the Thematic Approach as a theory of knowledge with an epistemological/gnosiological bias for the apprehension of themes. For this, it was necessary to initially carry out an epistemological analysis based on the German, Johannes Hessen and, through this, a gnosiological analysis based on the Brazilian educator, Paulo Freire. As methodological paths, three sources of data were used: bibliographic survey, interviews and analysis of materials. From these analyzes built on the basis of the Discursive Textual Analysis methodology, three categories emerged: I. Gnosiological elements necessary for the didactic-pedagogical process to understand the themes; II. Gnosiological elements that cross the apprehension of the themes; III. Gnosiological challenges and overcoming possibilities. Such categories demonstrated an answer to the problem, so that the contributions of the Thematic Approach to the apprehension of identified themes refer to the elements of - problematization, dialogicity, contextualization and interdisciplinarity - necessary to the didacticpedagogical process. In addition to these elements, when taking into account the students' primary culture for apprehending significant situations, a critical apprehension with potential for social transformation is generated. As limits, aspects about - didactic material, evaluations, curriculum structure and teacher training were pointed out. Based on these results, it was possible to reflect around the search for a critical, social, humanistic and reality-changing apprehension that the Thematic Approach proposes, as well as expressing challenges that need to be overcome. It is hoped that this study can serve as a contribution to future research and practices by educators who strive for quality education and believe in the transformative potential of education.